Early laparoscopic cholecystectomy is associated with less risk of complications after the removal of common bile duct stones by endoscopic retrograde cholangiopancreatography - Mehmet Aziret; Kerem Karaman; Metin Ercan; Erdem Vargöl; Bilal Toka; Yusuf Arslan; Volkan Öter; Erdal Birol Bostancı; Erkan Parlak (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Several studies recommend prompt laparoscopic cholecystectomy (LC) following endoscopic retrograde cholangiopancreatography (ERCP) for choledocholithiasis. However, histopathological alterations in the gallbladder during this time interval and the role played by ERCP in causing these changes have not been sufficiently elucidated. To compare early period LCs with delayed LCs following common bile duct stone extraction via ERCP with regard to operation time, hospitalization period, conversion to open cholecystectomy rate, morbidity, mortality, and histopathological alterations in the gallbladder wall. Materials and Methods: A total of 85 patients were retrospectively divided into three groups: early period LC group (48-72 h; n=30), moderate period LC group (72 h-6 weeks; n=25), and delayed period LC group (6-8 weeks; n=30). Results: The operation time was significantly shorter, and the total number of complication rates and hospital readmission was significantly less frequent in the early period LC group (p<0.05). Ultrasound showed a significantly thicker gallbladder wall (>3 mm) in the moderate and late period LC groups than in the early period LC group (p<0.001). Culture growth was significantly higher, and fibrosis/collagen deposition in the gallbladder wall with injury to the mucosal epithelium was significantly more frequently detected by histopathological examination in the moderate and late period LC groups than in the early period LC group (p<0.05). Conclusion: Early period LC following stone extraction by ERCP is associated with shorter operation time, fewer fibrotic changes in the gallbladder, and lower risk for the development of complications. Therefore, LC can be performed safely in the early period after ERCP. Cite this article as: Aziret M, Karaman K, Ercan M, et al. Early laparoscopic cholecystectomy is associated with less risk of complications after the removal of common bile duct stones by endoscopic retrograde cholangiopancreatography. Turk J Gastroenterol 2019; 30(4): 336-44.